Improving urban transport for the poor - Ian Thomson (CEPAL Review, 1993)
Even though Latin America and the Caribbean is the most urbanized and the least poor of the regions of the developing world, a quarter of the region’s population live, or rather exist, below the poverty line. Many of these are town or city dwellers, Many lower income families spend more than 15% of their income on urban public transport: a proportion which has been rising continuously over the past few decades because bus operating costs per passenger have increased as cities get bigger and car-created congestion has made each bus less productive.